1997
DOI: 10.1017/s026988899700101x
|View full text |Cite
|
Sign up to set email alerts
|

A review of machine learning

Abstract: This paper reviews Machine Learning (ML), and extends and complements previous work (Kocabas, 1991; Kalkanis and Conroy, 1991). Although this paper focuses on inductive learning, it at least touches on a great many aspects of ML in general. In addition, incremental induction is also reviewed. Therefore, a general review of ML is presented, but specific detail which has been covered previously is omitted, although other relevant references are noted, and later material is commented upon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 113 publications
0
21
0
2
Order By: Relevance
“…A Large number of classification techniques were developed by the means of statistical method, logical method , symbolic method, perceptron based method, fuzzy based concept, Neural network based and rule based etc. D. Dutton & G. Conroy et al [10] provided brief review of what Machine Learning algorithims has done. De Mantaras and Armengol also reported historical survey of logic and instance based learning classifiers [11].…”
Section: Introductionmentioning
confidence: 99%
“…A Large number of classification techniques were developed by the means of statistical method, logical method , symbolic method, perceptron based method, fuzzy based concept, Neural network based and rule based etc. D. Dutton & G. Conroy et al [10] provided brief review of what Machine Learning algorithims has done. De Mantaras and Armengol also reported historical survey of logic and instance based learning classifiers [11].…”
Section: Introductionmentioning
confidence: 99%
“…We have limited our references to recent refereed journals, published books and conferences. A brief review of what ML includes can be found in (Dutton and Conroy 1996). De Mantaras and Armengol (1998) also presented a historical survey of logic and instance based learning classifiers.…”
mentioning
confidence: 99%
“…Several machine learning algorithms (Dutton & Conroy, 1997) have been applied to interface agents. Memory-based learning (a kind of case-based learning), reinforcement learning and induction of decision trees (ID3) are used in scheduling agents (Kozierok & Maes, 1993;Mitchell et al, 1994).…”
Section: Usage Model Acquisition Methodsmentioning
confidence: 99%